Karateristik Tegangan Tembus Gas Karbondioksida (CO2) Dan Nitrogen (N2) Dibawah Tegangan Tinggi AC - Ginting, Rio Abraham; Murdiya, Fri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
In the power system, there are many aspects that must be considered to operate the system such as conductor, insulator, and the electric power apparatuses. In this research, we investigated the carbon dioxide and nitrogen gases as gas insulation candidate in the circuit breaker. It is shown that the breakdown voltage of CO2 and N2 is proportional with the gap of sphere electrodes. In order to comparison between CO2, N2 gases and SF6 gas, the breakdown voltage of CO2 and N2 is lower than the SF6. However, if CO2 and N2 gas pressure is 4 bar, the breakdown voltage of CO2 and N2 will be similar or above SF6 at pressure 1 bar.Keywords: carbon dioxide, nitrogen, electrode, breakdown voltage, circuit breaker.